Status Cerai Tidak Penting: Analisis Sosiologis Perempuan yang Tidak Menggugat Suaminya ke Pengadilan Agama - Silfia Yanasti (Jurnal Sosiologi Andalas, 2021)
Deciding to divorce is empowered by the goals to be achieved, because women have a need for that status. Some women don't need that status, which is why they don't file for divorce. The purpose of writing is to describe the causes of divorce status is not important for women whose marital status is not socially clear. This study tries to look at the experiences of women that lead to the meaning of divorce status. Feminist approach is used in this study, with qualitative research methods. Data were obtained through interviews with women in the study area. Through sociological analysis, women who do not file for divorce from their husbands to the Religious Courts are motivated by their situation that they do not experience financial difficulties because they work and are not stigmatized.